My eleventh integral problem

Calculus Level 5

0 π / 2 e x cos 2 x d x \large \displaystyle \int_{0}^{\pi/2} e^{x} \cos^{2} x \, dx

It is given that the above integral can be expressed in the form a e b π / c d f \large \dfrac{a e^{{b \pi}/{c}}-d}{f} where a , b , c , d , f a, b, c, d, f are positive integers, gcd ( a , f ) = gcd ( b , c ) = 1 \gcd(a,f) = \gcd(b,c) = 1 .

Find the value of a + b + c + d + f a+b+c+d+f .


The answer is 13.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Feb 14, 2016

0 π 2 e x cos 2 x d x = 1 2 0 π 2 e x ( 1 + cos ( 2 x ) ) d x = 1 2 0 π 2 e x d x + 1 4 0 π 2 e x ( e 2 x i + e 2 x i ) d x = 1 2 [ e x ] 0 π 2 + 1 4 [ e ( 1 + 2 i ) x 1 + 2 i + e ( 1 2 i ) x 1 2 i ] 0 π 2 = 1 2 ( e π 2 1 ) + 1 4 [ e x ( e 2 x i + e 2 x i 2 i e 2 x i + 2 i e 2 x i ) 1 + 4 ] 0 π 2 = 1 2 ( e π 2 1 ) + 1 2 × 5 [ e x ( cos ( 2 x ) + 2 sin ( 2 x ) ) ] 0 π 2 = 1 2 ( e π 2 1 ) + 1 10 [ e π 2 ( cos π + 2 sin π ) e 0 ( cos 0 + 2 sin 0 ) ] = 1 2 ( e π 2 1 ) + 1 10 ( e π 2 1 ) = 2 e π 2 3 5 \begin{aligned} \int_0^{\frac{\pi}{2}} e^x \cos^2 x \space dx & = \frac{1}{2} \int_0^{\frac{\pi}{2}} e^x \left(1+\cos (2x)\right) \space dx \\ & = \frac{1}{2} \int_0^{\frac{\pi}{2}} e^x \space dx + \frac{1}{4} \int_0^{\frac{\pi}{2}} e^x \left(e^{2xi} + e^{-2xi} \right) \space dx \\ & = \frac{1}{2} \left[e^x\right]_0^\frac{\pi}{2} + \frac{1}{4} \left[ \frac{e^{(1+2i)x}}{1+2i} + \frac{e^{(1-2i)x}}{1-2i} \right]_0^\frac{\pi}{2} \\ & = \frac{1}{2} \left(e^\frac{\pi}{2} - 1 \right) + \frac{1}{4} \left[\frac{e^x\left(e^{2xi} + e^{-2xi} - 2ie^{2xi} + 2ie^{-2xi} \right)}{1+4} \right]_0^\frac{\pi}{2} \\ & = \frac{1}{2} \left(e^\frac{\pi}{2} - 1 \right) + \frac{1}{2\times 5} \left[e^x \left(\cos (2x) +2 \sin (2x) \right) \right]_0^\frac{\pi}{2} \\ & = \frac{1}{2} \left(e^\frac{\pi}{2} - 1 \right) + \frac{1}{10} \left[e^\frac{\pi}{2} \left(\cos \pi + 2\sin \pi \right) - e^0 \left(\cos 0 + 2\sin 0 \right) \right] \\ & = \frac{1}{2} \left(e^\frac{\pi}{2} - 1 \right) + \frac{1}{10} \left(-e^\frac{\pi}{2} -1 \right) \\ & = \frac{2e^\frac{\pi}{2}-3}{5} \end{aligned}

a + b + c + d + f = 2 + 1 + 2 + 3 + 5 = 13 \Rightarrow a + b + c + d + f = 2+1+2+3+5 = \boxed{13}

Did it the same way (+1)!

Harsh Khatri - 5 years, 4 months ago

Nice approach! I did it without e e though.

Hobart Pao - 5 years, 4 months ago

Log in to reply

@Hobart Pao What do you mean?? Could you please elaborate...!!

Aaghaz Mahajan - 3 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...